2020
DOI: 10.18203/2349-2902.isj20205422
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge attitude practice study of diabetic retinopathy

Abstract: Background: Diabetic retinopathy (DR) is an important cause of visual impairment. It is preventable with proper screening and treatment of diabetes. Therefore, it is necessary to assess awareness of the disease in the population and educate them. Our study aimed to assess the knowledge, attitude and practices regarding diabetes and DR in India.Methods: We conducted a knowledge, attitude, and practice study of 1152 participants belonging to various economic backgrounds across India, using a validated questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…They are the ability of the drug to be present in the labelled amount and its availability to the body [5]. An oral tablet is meant to deliver the drug to the human body via the gastro-intestinal system in order to produce a therapeutic effect [6][7][8]. It had been reported that in many situations, the bioavailability of drugs from different manufacturers did not give the same therapeutic response [9].…”
Section: Introductionmentioning
confidence: 99%
“…They are the ability of the drug to be present in the labelled amount and its availability to the body [5]. An oral tablet is meant to deliver the drug to the human body via the gastro-intestinal system in order to produce a therapeutic effect [6][7][8]. It had been reported that in many situations, the bioavailability of drugs from different manufacturers did not give the same therapeutic response [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism for DR are not clear, but the most probable cause is intraocular formation of reactive oxygen species and protein kinase C activation that causes hyper permeability of the retinal blood vessels which deteriorate retinal blood flow, thickening of the basement membrane, leading to ischemia and cellular signaling by vascular endothelial growth factors causing ocular neovascularization which lead to retinal detachment and vitreous hemorrhage can occur. DR types include non-proliferative and proliferative diabetic retinopathy [17]- [19]. Proliferative DR is the most common sight-threatening complication of DM [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Early DR is asymptomatic, [21] therefore, coordinated treatment strategies are essential to prevent or limit the progression of DR. Such strategies include regular screening of DR risk factors, glycemic control, and rapid diagnosis of DR [8], [17], [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation